Technological developments of SMES systems in distribution networks - AKAR, ONUR (My University, 2023)
Today electric power has become one of the most significant requirements for vital activities. New energy sources have been found along with the depletion of the current energy sources and the development of the technology. Electric power has been generated from various energy sources and tried to be distributed to the consumers. At this stage, in the transmission of electric power to consumers from the generation center, distribution to consumers with the least loss and in a high-quality manner matters. In this case, the use of an energy storage system (ESS) is deemed an extensively applicable solution. Energy storage systems may store the electric power based on demand and if required, may provide the energy again. Due to the great potential of energy storage and the increasing development of the market, researches are performed on the types, implementations and evaluation systems of energy storage systems and the most suitable solution is presented. In order to provide high-quality electric power, one of the most reliable and cost-effective options for optimizing the efficiency and stability of transmission and distribution network systems is superconducting magnetic energy storage (SMES). SMES is a new technology used for regulating power fluctuations and preserving the stability of the network when great changes occur in load. This article refers to ESS and the types of storage systems preferred as per the system requirements, and additionally, it presents a comparison of its advantages and disadvantages. The SMES technology and its usage areas in the distribution networks were included and it was considered that a significant contribution would be made to the literature.
Keywords: Electric Power; Distribution Network; ESS; SMES